Adaptor regulation of LFA-1 signaling in T lymphocyte migration : potential druggable targets for immunotherapies? - Verma, Navin K. (2015)
The integrin lymphocyte function associated antigen-1 (LFA-1) plays a key role in leukocyte trafficking and in adaptive immune responses through interactions with adhesive ligands, such as ICAM-1. Specific blockade of these interactions has validated LFA-1 as a therapeutic target in many chronic inflammatory diseases, however LFA-1 antagonists have not been clinically successful due to the development of a general immunosuppression, causing fatal side effects. Growing evidence has now established that LFA-1 mediates an array of intracellular signaling pathways by triggering a number of downstream molecules. In this context, a class of multimodular domain-containing proteins capable of recruiting two or more effector molecules, collectively known as “adaptor proteins,” has emerged as important mediators in LFA-1 signal transduction. Here, we provide an overview of the adaptor proteins involved in the intracellular signaling cascades by which LFA-1 regulates T-cell motility and immune responses. The complexity of the LFA-1-associated signaling delineated in this review suggests that it may be an important and challenging focus for future research, enabling the identification of “tunable” targets for the development of immunotherapies.